Experiences of young adults with type 1 diabetes while using alcohol and recreational drugs: An interpretative phenomenological analysis (IPA) of semi-structured interviews. (July 2018) - Pastor, Adam; O'Brien, Casey L.; Teng, Jessie; Conn, Jennifer; Loh, Margaret; Collins, Lisa; MacIsaac, Richard J.; Bonomo, Yvonne
Highlights: The experiences of young adults with type 1 diabetes who use substances substances are reported. Interviews revealed specific concerns including episodes of hypoglycaemia. Harm reduction strategies have been developed by young adults with type 1 diabetes. Clinicians are the most trusted source of information but rarely used due to stigma. Abstract: Aims: Alcohol and recreational drug use is common in young adults with type 1 diabetes (T1DM) and may account for increased morbidity and mortality. This study explores the motivations and experiences unique to this population while using alcohol and recreational drugs. Methods: Semi-structured interviews focusing on substance use were performed with 16 young adults aged 18–35 with T1DM who drink alcohol (at least 50 g, 5 Australian standard drinks, in a single session) and/or used recreational drugs. A qualitative interpretative phenomenological analysis (IPA) of the interview data was performed by three clinicians with differing expertise (a psychologist, endocrinologist and addiction medicine specialist). Results: A range of motivations, experiences and harm reduction strategies regarding substance use were described specific to young adults with T1DM with most aimed at mitigating the risk of hypoglycaemia. Clinicians remained the most trusted resources, however, substance use was rarely discussed at clinical encounters. Currently available information, especially for illicit drugs, was described as inadequate. Conclusions: This analysis identified experiences unique to young adults with T1DM when using alcohol and other drugs. Understanding these experiences and how these young adults attempt to mitigate the risks of substance use may lead to improved clinical interactions and management strategies.